Impact of chronic and pulse dilution disturbances on metabolism and trophic structure in a saline Mediterranean stream - Gutiérrez-Cánovas, Cayetano; Hernández, Juan; Millán, Andrés; Velasco, Josefa (Hydrobiologia, 2012)
Predicting the consequences of global change involves investigating the mechanisms by which anthropogenic stress modifies ecosystem function. In this sense, naturally stressed ecosystems provide a new framework to test hypotheses in such a context. Here, we use a saline stream (Rambla Salada, SE Spain) as a study case to test the general hypothesis that chronic stress has stronger impacts on metabolism and trophic structure than pulse disturbances. We compared two reaches differing in the persistence of dilution stress over the course of 2 years: the chronically disturbed reach was subject to persistent dilution (chronic disturbance) by freshwater inputs from surrounding irrigated crops and presented a dense stand of the common reed Phragmites australis ; and the reference reach , which presented pristine conditions. During the first study year, both reaches were affected by several freshwater inputs due to a diversion channel break (pulse disturbance) that significantly decreased conductivity. During the second year, conductivity recovered to mean pre-pulse disturbance levels. Pulse dilution disturbance had no significant effect on production:respiration ratios ( P / R ), although predator biomasses increased. However, chronic dilution significantly decreased P / R values as well as consumer and producer biomasses. Dilution disturbances had no significant effects on the relative importance of the different functional feeding groups. Isotopic signatures revealed that macroinvertebrates in both reaches relied upon aquatic autotrophs, despite the common reed inputs at the chronically disturbed reach . In summary, this study highlights the relevance of stress persistence and the usefulness of functional measures when aiming to predict disturbance effects. Thus, whilst pulse disturbances had minor effects on ecosystem function, chronic dilution produced biomass depletion and a change from an autotrophic to a heterotrophic ecosystem.